Herbaceous cover management in olive groves can be important for aerial-feeding birds. A case study in southern Spain - Navarro, Inmaculada; Farfán-Aguilar, Miguel Ángel; Fa, Julia E.; Román Muñoz, Antonio (ELSEVIER, 2025)
The European Olive (Olea europaea) is a widely cultivated tree throughout the Mediterranean Basin where it plays an important economic, social and cultural role. Given the extensive area occupied by olive groves, which are known to be ecologically important for many animals, species diversity and abundance may be affected by the type of herbaceous vegetation management applied. Here, we investigate the effect of vegetation treatment (mechanical or chemical management of herbaceous cover, or bare soil) on bird abundance with a particular focus on six aerial-feeding (AF) bird species – Common (Apus apus) and Pallid Swifts (A. pallidus), Alpine Swift (Tachymarptis melba), Barn Swallow (Hirundo rustica), Red-rumped Swallow (Cecropis daurica), and the Common House Martin (Delichon urbicum). Using point counts, we recorded all birds (AF and non-AF birds) heard and observed in three separate olive grove plots subjected to the different herbaceous cover treatments. Our results show that plots with herbaceous cover hosted a higher number of bird species, including insectivorous and AF species, as well as a greater abundance of total birds, insectivorous birds, and AF birds, compared to the bare soil plot. The abundance of AF bird was significantly higher in the two plots with herbaceous cover compared to the plot with bare soil. During the post-nuptial migration period, AF birds—together with other species—were also among the dominant species in the two plots with herbaceous cover, whereas in the bare soil plot, none of the six species was dominant. Our results suggest that olive groves can be important for AF birds, a group not traditionally included in studies of bird communities in olive farms. We suggest that farmers and policy makers, as the main actors in olive farming, should consider the impact of the different management techniques on AF bird populations.
Keywords: Agricultura; Biología de la conservación; Biodiversidad; Malas hierbas - Control; Aves insectívoras; Pesticidas - Aspectos ambientales; Agricultura sostenible; Medio ambiente - Gestión; Agriculture; Biodiversity; Herbaceous cover; Insectivorous birds; Pesticides; Sustainability